Metabolic profile of main organic acids and its regulatory mechanism in solid-state fermentation of Chinese cereal vinegar. (July 2021) - Wu, Yanfang; Xia, Menglei; Zhao, Nan; Tu, Linna; Xue, Danni; Zhang, Xianglong; Zhao, Cuimei; Cheng, Yang; Zheng, Yu; Wang, Min
Graphical abstract: Highlights: Organic acids metabolism profile in solid-state fermentation of vinegar was revealed. Metabolism of acetic acid shifted from acetyl-P to acetaldehyde pathway. Metabolism of lactic acid shifted from pyruvate to L-lactaldehyde pathway. The core microorganisms involved in acetic acid and lactic acid metabolism evolved. The metabolism of key organic acids was regulated by temperature and acetic acid. Abstract: Shanxi aged vinegar (SAV), a traditional Chinese cereal vinegar, is produced using solid-state fermentation (SSF) technology. Organic acids are the key flavor compounds of vinegar. However, the metabolic mechanism of organic acids during SSF process is still unclear. In this study, metatranscriptomics was used to explore the metabolic profile of main organic acids in SSF. The results show that carbon metabolism is the dominant pathway during fermentation, among which pyruvate metabolism, glycolysis and starch and sucrose metabolism associated with organic acids were the most abundant. The metabolic pathways of acetic acid and lactic acid shift from acetyl-P and pyruvate pathways at early and middle-early stages of fermentation to acetaldehyde and L-lactaldehyde pathways at later stages, respectively, and Lactobacillus and Acetobacter are the predominant microorganisms contributed to them. Temperature and acetic acid are proven to be the environmental factors that regulate the metabolic activity during SSF. This study sheds new lights on metabolism of flavor substances in the spontaneous ecosystems of traditional fermented food.